Relationship between Oil and Stock Markets: Evidence from Pakistan Stock Exchange - Hanif, Muhammad (International Journal of Energy Economics and Policy, 2020)
This study documents the impact of price variations in global markets, specifically oil, on stock returns at Pakistan Stock Exchange (PSX). We select three global markets (oil, gold and currency exchange) and two PSX indices [conventional and Islamic] for a period 2009-20 to provide evidence. Monthly data for the selected time series is used for analysis. Analysis techniques include descriptive statistics, stationarity testing, Johansen cointegration, correlation and regression analysis. Findings suggest joint long-run co-movements of selected markets. Regression results indicate the significance of oil prices at 1% level, with positive signs, in the stock return generation process at PSX [for both indices conventional and Islamic]. Other selected markets (gold and currency exchange) are although significant but at a higher degree, with negative signs. For the oil market, results confirm the demand-pull inflation hypothesis in Pakistani market. Results also confirm shifting to gold market by investors in the period of reductions in stock returns. Finally, depreciation of domestic currency discourages investors in buying stocks. We recommend investors to have an eye on oil, gold and currency markets while making investment decisions at PSX. We also recommend to policymakers to take timely actions for exchange rate stability, to avoid the outflow of capital. To the best of our knowledge, this is the only study documenting the influence of global markets on stock returns at PSX in recent years. Keywords: Oil prices; Gold market; exchange rate; Stock market; Pakistan JEL Classifications: G10, G11, G12 DOI: https://doi.org/10.32479/ijeep.9653